Physiological comparison between mulberry (Morus alba L.) Leaves diet and artificial diet on growth development as well as antibiotic therapeutic response of silkworms - Pimporn Anantaworasakul (2018)
Silkworm has been proposed recently as an animal model for the study of therapeutic effects of drug candidates. Little is known regarding the factors influencing the physiology of the silkworm, and this might become the major effect of the therapeutic result interpretation. In the present study, the effect of a diet of mulberry leaves as compared to an artificial diet on Thai silkworm growth development as well as the antibiotic therapeutic responses of bacterial infected silkworms is explored. The silkworms fed with mulberry leaves as well as those with artificial diets were weighed and the numbers of survival were counted. The mulberry leaves- fed silkworms (MFS) showed faster growth rate (0.2 g body weight day-1) than the artificial diet-fed silkworms (AFS). The MFS exhibited bigger body size and greater body weight than the AFS. It was found that the median lethal dose (LD50) of Staphylococcus aureus cells needed to kill 1-g body weight silkworms was 108 cells ml-1 for both MFS and AFS. However, the median effective dose (ED50) of the antibiotics (ampicillin, ceftriaxone, cephalexin, and gentamicin) for AFS was two times higher than those for MFS. The results indicate that some elements in mulberry leaf affect the therapeutic effect of the antibiotics in the silkworm model. This study suggests that high attention on silkworm diet should be paid to the research relevant to drug therapeutic evaluation using silkworms as an animal model.